Satu Tinjauan Tentang Persepsi Guru-Guru Terhadap Program Latihan Dalaman Yang Dijalankan Di Sekolah-Sekolah - Khairul Azman, Mohd. Suhaimy (1997)
The study intended to examine the perception of teachers toward importance, implementation and supervision of in house training program and the relationship between variables (importance with implementation and implementation with supervision) of in house training program. The objectives of this study are to observe 1) the difference in perception of the importance in house training among teachers’ gender, 2) the difference in perception of the importance in house training among teachers’ service scheme, 3) the difference in perception of the importance in house training among grade A and B school teachers’, 4) a significant relationship among the importance and implementation variables and 5) a significant relationship among the implementation and supervision variables of in house training program. 80 respondents were selected from six secondary schools in Kubang Pasu, Kedah. A set of questionnaire with five Likert Scale was distributed. The collections of the data is to study the perception of teachers and the relationship among the variables. The questionnaire was adapted from research done by Matnoh (1995), Mohd Radzi (1995) and a few questions were created by the researcher. All the data gathered was analyzed at p = .05 using Descriptive Statistics and Pearson Correlations. The results indicate that there are 1) no significant different in perception toward in house training program between teachers’ gender (p > .05 p = .366), service scheme (p > .05 p = .322) and school grade (p > .05 p = .240), 2) a strong relationship and significant (r = .739 p = .OO) between importance and implementation variables. There is a weak relationship and not significant (r = .270 p = 0.16) between implementation and supervision variables of in house training program. Based on the findings, the researcher would like to suggest that the process of implementation and supervision of in house training program will be emphasized and upgraded so that they will benefit the organization and the staffs.